Clinical practice guideline for the screening, diagnosis, and management of chronic kidney disease stages 1-3 for the Peruvian Social Security (EsSalud) - Bravo-Zúñiga, Jessica (2020)
This paper summarizes the clinical practice guidelines (CPG) for the screening, diagnosis, and management of patients with chronic kidney disease (CKD) stages 1-3 in the Social Security of Peru (EsSalud). A guideline development group (GDG) was established for develop this CPG, which included clinical and methodology specialists, who formulated 08 clinical questions. Systematic searches of systematic reviews and, when considered necessary, primary studies were conducted to answer each question; and relevant evidence was selected. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the GDG used the GRADE methodology for reviewing the evidence and for developing recommendations. At the end, this CPG formulated 08 recommendations (04 strong and 04 conditional), 29 points of good clinical practice, and 03 flowcharts were formulated.